1968
DOI: 10.4039/ent100801-8
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonal Movements of Wireworms (Coleoptera: Elateridae) in Relation to Soil Moisture and Temperature in the Organic Soils of Southwestern Quebec

Abstract: A 4-year study in the virgin organic soils of southwestern Quebec revealed that most elaterid larvae moved from the subsurface to the top 10 in. of soil in early May, when the soil temperature at a depth of 4 in. was approximately 35°F. This upward movement readied its peak when the topsoil moisture content was 200% and the soil temperature at 4 in., 55°F. In early June, when the soil temperature reached 67°F, the larvae began to move downward and very few larvae were found in the first top layers of soil when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 3 publications
3
15
0
Order By: Relevance
“…Ctenicera destructor and Hypolithus bicolor, two commonly co-occurring wireworms in Canada, have significantly different ranges of optimal temperatures for activity that are based on laboratory studies (115). These findings have been corroborated in field studies with numerous wireworm species (11,30,54,61,116). Species-specific preferred temperature ranges have also been reported for scarab grubs, from both correlative field (98) and laboratory studies (105).…”
Section: Response To Temperaturesupporting
confidence: 64%
See 1 more Smart Citation
“…Ctenicera destructor and Hypolithus bicolor, two commonly co-occurring wireworms in Canada, have significantly different ranges of optimal temperatures for activity that are based on laboratory studies (115). These findings have been corroborated in field studies with numerous wireworm species (11,30,54,61,116). Species-specific preferred temperature ranges have also been reported for scarab grubs, from both correlative field (98) and laboratory studies (105).…”
Section: Response To Temperaturesupporting
confidence: 64%
“…Early workers correlated changes in moisture conditions with the occurrence, persistence, and damage potential of soil insects in the field (51,61,98,115).…”
Section: Response To Moisturementioning
confidence: 99%
“…Although there have been field studies that look at the movement of soil insects over Long periods (Forbes 1907, Griddle 1918, McCollock & Hayes 1923, Mail 1930, Dowdy 1944, Hawley 1949, LaFrance 1968, Fisher et al 1975, these studies considered the soil insects found i n the top 5 cm as being at the surface layer. Detailed k110w1-edge of the movement of grubs within the top 5 cm over short periods can have a profound effect on pest management.…”
Section: Radiography In Soil Insect Researchmentioning
confidence: 99%
“…migrated rapidly out of dry sand in favour of wet sand, due entirely to the differential effect of moisture on burrowing activity. Lafrance (1968) conducted a 4-year study of the seasonal movements of populations of mixed wireworm species (including Agriotes mancus (Say) and a range of other genera) in organic soils in Quebec. This study showed that most wireworms moved from deeper in the soil pro®le to the top 20 cm when 10 cm soil temperatures reached » 3°C.…”
Section: Spatial Distributionmentioning
confidence: 99%